Epigenetics in ecology and evolution. (9th February 2020) - Herrel, Anthony; Joly, Dominique; Danchin, Etienne
Abstract: The discovery of the multidimensional nature of the inherited information carried by the epigenome and the characterization of its intra‐ and intergenerational dynamics have profoundly changed our understanding of the functioning of biological organisms and the origins of phenotypic diversity. This has raised considerable interest in the study of epigenetics which is emerging as a 'missing link' between environmental and phenotypic variation. Recent discoveries have provided important insights into the mechanisms of phenotypic plasticity, inheritance and adaptation; key concepts at the crossroads of individual‐centred approaches (that mostly study proximate mechanisms); and supra‐individual ones (that mostly study ultimate processes). In this context, epigenetics emerges as a major source of inquiry for the study of ecological and evolutionary dynamics. This special feature provides an overview of the role of epigenetics in ecology and evolution.